Differentiating COPD and asthma using quantitative CT imaging and machine learning - Moslemi, Amir; Kontogianni, Konstantina; Brock, Judith; Wood, Susan; Herth, Felix; Kirby, Miranda (The European respiratory journal, 2022)
Background There are similarities and differences between chronic obstructive pulmonary disease (COPD) and asthma patients in terms of computed tomography (CT) disease-related features. Our objective was to determine the optimal subset of CT imaging features for differentiating COPD and asthma using machine learning. - Methods COPD and asthma patients were recruited from Heidelberg University Hospital (Heidelberg, Germany). CT was acquired and 93 features were extracted: percentage of low-attenuating area below −950 HU (LAA950), low-attenuation cluster (LAC) total hole count, estimated airway wall thickness for an idealised airway with an internal perimeter of 10 mm (Pi10), total airway count (TAC), as well as airway inner/outer perimeters/areas and wall thickness for each of five segmental airways, and the average of those five airways. Hybrid feature selection was used to select the optimum number of features, and support vector machine learning was used to classify COPD and asthma. - Results 95 participants were included (n=48 COPD and n=47 asthma); there were no differences between COPD and asthma for age (p=0.25) or forced expiratory volume in 1 s (p=0.31). In a model including all CT features, the accuracy and F1 score were 80% and 81%, respectively. The top features were: LAA950, outer airway perimeter, inner airway perimeter, TAC, outer airway area RB1, inner airway area RB1 and LAC total hole count. In the model with only CT airway features, the accuracy and F1 score were 66% and 68%, respectively. The top features were: inner airway area RB1, outer airway area LB1, outer airway perimeter, inner airway perimeter, Pi10, TAC, airway wall thickness RB1 and TAC LB10. - Conclusion COPD and asthma can be differentiated using machine learning with moderate-to-high accuracy by a subset of only seven CT features. - Tweetable abstract ERSpublications - click to tweetAsthma and COPD can be differentiated with high accuracy using a subset of only seven CT features by machine learning. Reduced CT emphysema and total airway count play an important role in distinguishing patients with asthma from COPD. https://bit.ly/3gOW6rq